Размножение зайца-русака (Lepus europaeus Pall.) в Белоруссии - Гайдук, В.Е. (Вестник зоологии, 1973)
Investigation resulted in establishing that in the Byelorussia the season of L. europaeus reproduction lasts from February to September. For this period a female gives 2-4 litters, 9.5 young hares at an average. The second and third litters which give 69.4% of new-borns are of greatest significance for the growth of populations. In the hunting season there is 1.1. (0.9-1.4) of young hares per adult one.